Palm leaves reinforced calcium carbonate/adhesive/polyaluminium chloride as a potential roofing material - Abu Hassan, Muhd. Hafiz; Wan Abdul Rahman, Wan Aizan (2007)
Composites of adhesive/ calcium carbonate/polyaluminium chloride-PAC/ based waste material reinforced with oil palm leaves fibers have been prepared. Roofing components were produced with these composites through a simple and low-energy consuming method. Plant fibers, which are widely available in most developing countries, can be used as convenient materials for brittle matrix reinforcement, even though they present relatively poor durability performance. Taking into account the fibers mechanical properties, with an adequate mix design, it is possible to develop a material with suitable properties for building purposes. In order to improve the durability of plant fibers (oil palm leaves fiber), this paper presents the approach adopted in the research which is directed towards the development of alternative binders, with controlled free waste (Adhesive/ Calcium carbonate/ Polyaluminium chloride-PAC). Palm leaves fibers demonstrate to be more suitable plant fibers for the reinforcement of large components as can be proved by in-use durability performance and several tests. More recently, pulp from eucalyptus waste and residual sisal and coir fibers have been studied as a replacement for asbestos in roofing components. The result has shown 10wt% of fiber is the optimal loading for composites where its characteristics quite satisfy and further loading beyond the level has caused an adverse result on the properties.